The effectiveness and safety of acupuncture for post-stroke depression: An overview of systematic reviews - Run-qing Miao; Feng-ya Zhu; Tian-yu Wang; Shao Yin; Chen Shuai; Tao Li; Zhi Li; Lan Luo; Bin Yang (Complementary Therapies in Medicine)
Background: In recent years, research on acupuncture for post-stroke depression (PSD) has grown significantly, yet findings remain inconsistent. Few researchers have conducted comprehensive assessments of systematic reviews (SRs) in this area. Consequently, there is a need for a thorough and objective synthesis of clinical evidence regarding acupuncture's effectiveness in treating PSD. Objective: To evaluate and synthesize evidence on the efficacy and safety of acupuncture for PSD through systematic reviews, offering valuable insights for clinical practice and guiding future research directions. Methods: We searched PubMed, Embase, Web of Science, Cochrane Library, CNKI, SinoMed, Wanfang, VIP and Google Scholar databases for relevant literature. The search covered publications from database inception to September 10, 2024. Literature selection and data extraction were independently performed by two reviewers. The methodological quality, bias risk, and evidence level of included SRs were assessed using AMSTAR 2, ROBIS, and GRADE tools. The corrected covered area (CCA) was calculated to assess overlap in original studies. Data from included SRs were subjected to quantitative or descriptive analysis. Results: A total of 38 SRs on acupuncture for PSD were included. After assessment using AMSTAR 2, one SR was rated as moderate quality, two as low quality, and 35 as very low quality. According to ROBIS, 21 SRs were classified as high risk of overall bias, and 17 as low risk. Acupuncture showed potential to improve depressive symptoms, stroke-related symptoms, and activities of daily living in PSD patients, though the quality of evidence is limited. Some studies suggested possible effects on cognitive function, biomarkers, sleep quality, and Traditional Chinese Medicine syndromes, but these findings require further validation with higher-quality research. While no serious adverse effects were reported in the reviewed studies, more rigorous safety evaluations are needed before definitive conclusions about acupuncture's safety for PSD can be made. Conclusion: Acupuncture shows potential as a treatment for PSD, though more high-quality research is needed to establish its effectiveness and safety. Currently, the majority of systematic reviews exhibit deficiencies in protocol pre-registration, documentation of excluded studies, and disclosure of funding sources, resulting in systematic reviews of suboptimal quality. Current evidence suggests possible benefits for depressive symptoms, stroke-related symptoms, activities of daily living, cognitive function, biomarkers, sleep quality, and TCM syndromes, but these findings should be interpreted cautiously given the limitations in study quality. Further high-quality studies are needed to confirm the efficacy and safety of acupuncture for PSD.